Pokutna peregrinatio we wczesnym średniowieczu - Chłopowiec, Michał (Vox Patrum, 2018)
Pilgriming is generally understood as a kind of motivational, religious mowing to “saint places” revived by the atonement intention (to rarely thankful) for God given goodness, which is subjectively believed to be meaningful. In thereby interpretation, only visible aspect comes to the foreground, without getting into its theological proof. In hereby elaboration, however, the topic of theological issue is touched upon, not in a sense of a detailed meaning of the notion, but by showing the historical determinations conditioning the way of understanding the notion. In Christian bastion of the discussed phenomenon is the Middle East, from where the solutions have been transferred to the West, in somewhat different categories. The transfer, both in theory and in practice, could be possible only due to people’s engagement, who were fascinated with the eastern spirituality. Some of the famous names, who could be distinguished are Jerome, John Cassian or Melania the Elder, the most active figures. The idea of pilgrimage transferred to the west, hasn’t been, clearly, intact in its form, but exposed to, based on different local accents, evolutionary changes. It is shown in interpretation changes applied, in reference to the notion of peregrinatio, inland and in the British Isles.